A longitudinal study: studying parental mental state talk towards children in Singapore - Lor, Terese Yue Jia (Nanyang Technological University, 2024)
Parental talk, specifically mental state talk (MST), is related to children’s cognitive and social emotional development. However, there is limited research on MST in the context of Singapore. This current study therefore examined the relationships between MST and children’s age, children’s gender, and contexts. A total of 56 parent-child dyads participated in a longitudinal study when children were 5 to 8 months old and later when children were 16 to 18 months old. Parent-child dyads read a book together and their interactions were recorded at both time points. Parent-child conversations were then transcribed and coded into mental state talk (e.g., desire, emotion) and non-mental state talk (e.g., behaviour). Results showed that emotion talk, other mental states talk, and behaviour descriptions talk were significantly different across the two time points. There were no significant differences in parental MST towards daughters and sons at both time points. Repeated measures ANOVA found a higher frequency of parental MST and non-MST in the book-reading context than in the free-play context in the longer term, and found no differences in the shorter term. Research findings and implications related to parenting practices were then discussed.